Adalimumab biosimilars in the therapy of Crohn´s disease and ulcerative colitis: Prospective multicentric clinical monitoring - Wasserbauer, Martin; Hlava, Stepan; Drabek, Jiri; Stovicek, Jan; Minarikova, Petra; Nedbalova, Lenka; Drasar, Tomas; Zadorova, Zdena; Dolina, Jiri; Konecny, Stefan; Kojecky, Vladimír; Kozeluhova, Jana; et al. (PloS one, 2022)
OBJECTIVE: The adalimumab biosimilars FKB327 and GP2017 were approved for the therapy of patients with inflammatory bowel disease (IBD). Relatively few prospective studies with biosimilar adalimumab in patients with IBD have been published. The aim of this prospective observational study was to evaluate the effectiveness and safety of the biosimilar adalimumab. MATERIAL AND METHODS: Adalimumab biosimilars FKB327 (Hulio®) and GP2017 (Hyrimoz®) were indicated to 50 naive patients in terms of biological therapy with Crohn's disease (CD) or ulcerative colitis (UC). Effectiveness of therapy was evaluated via the Crohn's Disease Activity Index [CDAI] or the Mayo Scoring System [MSS] in patients with CD or UC, respectively, before and after 12 weeks. Additional goals were to evaluate weight changes, laboratory tests and complications or adverse events of this therapy. RESULTS: In CD patients, remission (CDAI <150) was achieved in 73.5% of cases, partial response (≥70-point decrease in CDAI score from baseline) in 11.8%, no response in 11.8% and 2.9% patients discontinued therapy. In UC patients, remission (total score on partial Mayo index ≤2 points) was achieved only in 18.8% of cases, partial response (≥2-point decrease in partial Mayo score from baseline) in 43.8%, no response in 25.0% and 12.5% patients discontinued therapy. There were statistically significant improvements in CDAI, MSS, haemoglobin, fecal calprotectin, albumin and CRP serum levels after 12 weeks of therapy. Seven adverse events were identified, three of which resulted in therapy being discontinued. CONCLUSIONS: This prospective observational study proved the effectiveness of the adalimumab biosimilars FKB327 and GP2017 in IBD.
Keywords: Crohnova nemoc; biosimilární léčivé přípravky; Adalimumab; indukce remise; idiopatické střevní záněty; Humans; výsledek terapie; Crohn Disease; Inflammatory Bowel Diseases; prospektivní studie; lidé; ulcerózní kolitida; Colitis, Ulcerative; Treatment Outcome; Biosimilar Pharmaceuticals; adalimumab; Remission Induction; Prospective Studies